PENINGKATAN KAPASITAS DAN EFISIENSI PEMBERIAN PAKAN IKAN MELALUI TEKNOLOGI FISH FEEDER PADA MASYARAKAT DUSUN PAITON DESA PARIJATAH KULON - Lusi, Nuraini; Afandi, A; Utami, S W (JURNAL WIDYA LAKSANA, 2020)
Based on the results of a survey in the village of Parijatah Kulon, Srono subdistrict, there are communities that conduct freshwater fish farming. One of the activities that must be carried out by farmers is feeding fish four times a day which is done conventionally by spreading feed from the pond side and is carried out continuously until the fish stop eating. This method is less effective because wasted feed will have an unfavorable impact on water conditions, and the energy and time used is less effective and efficient due to the limitations of farmers in determining the throwing distance, so it requires time to throw feed from one side to another pond so can provide even feed. The method used in this Community Service (PKM) activity is through the procurement of automatic fish feeder with a capacity of 30-40 kg with automatic fish feeder technology, training on how to use the equipment, maintenance and repair.